Waldenstrom's Macroglobulinemia and Peripheral Neuropathy, Organomegaly, Endocrinopathy, Monoclonal Gammopathy, and Skin Changes with a Bleeding Diathesis and Rash. (25th December 2013) - Haider, S.; Latif, T.; Hochhausler, A.; Lucas, F.; Abdel Karim, N.
Abstract : We report a case of a 29-year-old male who presented with paraesthesia and skin lesions with excessive bleeding after skin biopsy leading to hematology consultation. He was found to have prolonged partial thromboplastin time (PTT) and monoclonal gammopathy on serum protein electrophoresis (SPEP). He experienced excessive bleeding leading to hospitalization after bone marrow biopsy and required blood transfusion. He was diagnosed with Waldenstrom's Macroglobulinemia (WM), based on the presence of IgM- κ type monoclonal (M) protein and infiltration of lymphoplasmacytic cells identified in bone marrow aspirates. He was noticed to have features of peripheral neuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS syndrome). This is a very rare case of WM with POEMS syndrome which responded to chemotherapy using bortezomib, steroids, and rituximab.